EFFECT OF BARLEY CULTIVATED FOR DIFFERENT TIMES AS SUPPLEMETED DIET IN SOME PRODUCTIVE TRAITS OF BROILER CHICKENS - & et al., Al-Gharawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The present study was conducted to evaluate the effect of using barley cultivated in different times on performance and carcass parameters of broilers. A total of 300 day- old chicks of Ross 308 strain was used. Chicks were randomly allocated for four treatments groups with 75 chicks per treatment and 25 chicks for each replicate. The four treatments was follows: T1, control (no barley added), T2, barley cultured for six days, T3 barley cultured for seven days and T4, barley cultured for eight days. Results showed that the significant (P<0.05) improvement in body weight, weigh gain, feed conversion, Feed conversion ratio, carcass yield without giblet, relative weights of heart, liver and gizzard as well as ,relative weight of breast, thigh and drums ticks. Whereas, the relative weights of back, wings, neck and mortality was reduced significantly (p<0.05)due to barley cultivated supplementation compared with control group. ,cated for four treatment, strain was usod. Che effact